Existe relação da amplitude de distribuição das hemácias com a presença e gravidade da pré-eclâmpsia? - Naves, Welington Ued (2016)
Introduction: Preeclampsia is one of the main causes of the maternal and perinatal mortality all over the world. The relationship between the amplitude of red cells distribution (Red Cell Distribution Width – RDW) and arterial hypertension is already well documented, though there is a shortage of data relating RDW with preeclampsia. Methods: Analytical observational study conducted in the years 2014 and 2015, composed by 108 patients in the study group (50 mild preeclampsia and 58 severe preeclampsia) and 101 patients in the control group. The hemoglobin, RDW, platelets and other hematological indices were measured as part of the automated hemogram. Results: There was no difference in RDW between the pregnant women in the control group and the ones in the mild preeclampsia group (14,68 ± 1,64 vs. 14,22 ± 1,87), the control group and the severe preeclampsia group (14,68 ± 1,64 vs. 14,24 ± 1,78) and the control group and preeclampsia group (14,68 ± 1,64 vs. 14,23 ± 1,81). Conclusion: The levels of maternal serum RDW are not associated with the presence of preeclampsia and the levels of its severity.